Efeito da clorexidina na cicatrização umbilical de avestruzes - Silva, Valéria Maria Savoya da [UNESP]; Garcia Neto, Manoel; Perri, S.h.v.; Bechara, Gervasio Henrique (My University, 2010)
The contamination of the umbilical region of newly hatched ostriches is one of the major problems in the bird production. This work aimed to evaluate the umbilical healing of ostriches (Struthio camelus) through the use of chlorhexidine as antiseptic associated to the total or partial umbilical cord cut off. It was used 168 newly hatched ostriches of which the umbilical cords were either sectioned totally or 0.5 cm above their insertion. The umbilical region antisepsis consisted of topical administration of an aqueous or alcoholic solution of chlorhexidine, 0.5, 1.0 or 2.0% during three days. A group of non-treated animals was added also. The umbilical healing was evaluated in the ostriches at 14 and 28 days of age. Results showed that all the chlorhexidine solutions reduced the risk of omphalitis, being the alcoholic solution 2% the most efficient. Umbilical healing was faster in animals in which the umbilical cord was totally cut off. It can be concluded that the use of chlorhexidine as antiseptic for newly hatched ostriches is safe and favors the umbilical healing. Moreover, for a better effectiveness it is necessary to remove the umbilical cord in its insertion

Um dos maiores entraves na criação de avestruzes é relacionado à contaminação da região umbilical de avestruzes recém-eclodidos. Neste trabalho, objetivou-se avaliar a cicatrização umbilical de avestruzes (Struthio camelus) mediante a antissepsia com clorexidina associada à secção total ou parcial do cordão umbilical. Foram utilizados 168 filhotes, cujo cordão umbilical foi seccionado totalmente ou 0,5 cm acima da sua inserção. A antissepsia da região umbilical consistiu na aplicação de clorexidina, em solução aquosa ou alcoólica, nas concentrações de 0,5%, 1,0% e 2,0%, durante três dias. Também foi incluído um grupo sem tratamento. A cicatrização umbilical foi avaliada aos 14 e 28 dias de idade do filhote. Os resultados mostraram que as soluções de clorexidina reduziram o risco de onfalite, sendo a solução alcoólica 2% a mais eficiente. A cicatrização foi mais rápida nas aves em que o cordão umbilical foi seccionado totalmente. Conclui-se que o uso de clorexidina para a antissepsia da região umbilical de avestruzes recémeclodidos é seguro e favorece a cicatrização umbilical, sendo necessário para uma maior efetividade remover o cordão umbilical na altura da sua inserção.
The effect of chlorhexidine on the umbilical healing of ostriches
Keywords: Disinfection; Healing; Omphalitis; Struthio camelus; Cicatrização|Desinfecção; Onfalite; Struthio camelus